Concept of Moral and Etics in the Profession of Judges When Making Decission in A Case - Aggraini, Rina; Fatmasari, Reka; Fahira, Meida Anggi; Syawaludin, Syawaludin (Faculty of Sharia, IAIN Metro, 2022)
Discourses about professional ethics of judges started out from the reality of law enforcement officials (especially judges) that ignore the values of morality. Although the professional actors (judges) already have a professional code of ethics as a moral standard, apparently it has not had a positive impact, especially not being able to change the negative image of society on the face. One way to uphold the rule of law is to uphold ethics, professionalism, and discipline. The code of ethics of the judges profession in principle contains moral values ​​that underlie professional personality, namely freedom, justice and honesty.